Multiple spinal schwannomas of multiple intradural extramedullary tumors: a case report - Mewara, Deepak; Jain, Vartika; Hritika; Gupta, Abhishek Kumar; Singh, Nisha; Kundan; Shukla, Shiwani; Kumar, Pintu (International Surgery Journal, 2024)
We describe the case of a 30-year-old male patient who was brought to the hospital's general surgery department with a four-month history of low back pain, numbness, and paraesthesia in both legs, history of weakness in both legs is also present. Magnetic resonance imaging revealed multiple Intradural extramedullary tumors at the C3/C4, D1-D2, D4, and D8 levels- likely nerve sheath tumors (schwannomas). The patient underwent surgery for the removal of tumors. The diagnosis was validated by histopathological examination. Post-operative recovery was uneventful and the patient improved gradually and recovered fully in 10-15 days.